2017
DOI: 10.1111/jvh.12725
|View full text |Cite
|
Sign up to set email alerts
|

HIV/HCV coinfection and the risk of cardiovascular disease: A meta‐analysis

Abstract: The emergence of improved antiretroviral therapy has increased the life expectancy of human immunodeficiency virus (HIV)-infected individuals, although there is an increased susceptibility to developing cardiovascular diseases (CVD). The risk for CVD is purported to be even higher among people with HIV and hepatitis C virus (HCV) coinfection because of the increased inflammatory response, which may synergistically impact CVD risk. However, studies comparing CVD outcomes between HIV alone and HIV/HCV individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 40 publications
0
38
0
2
Order By: Relevance
“…In this study, HCV infection (active or cleared) was associated with CMBs, similar to what was previously reported in association with ICH in PWH . Although the incidence of CMBs in the HCV‐infected population has not been specifically investigated, it is well established that HCV infection has both neurovascular and cardiovascular toxicity as a consequence of chronic inflammation and accelerated atherosclerosis resulting from viral replication within vascular plaques and cerebral endothelial cells . In addition, HCV eradication reduces risk of ischaemic and haemorrhagic stroke .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, HCV infection (active or cleared) was associated with CMBs, similar to what was previously reported in association with ICH in PWH . Although the incidence of CMBs in the HCV‐infected population has not been specifically investigated, it is well established that HCV infection has both neurovascular and cardiovascular toxicity as a consequence of chronic inflammation and accelerated atherosclerosis resulting from viral replication within vascular plaques and cerebral endothelial cells . In addition, HCV eradication reduces risk of ischaemic and haemorrhagic stroke .…”
Section: Discussionmentioning
confidence: 99%
“…A large body of literature has linked CVD to chronic infection with hepatitis C virus (HCV), a common viral infection impacting an estimated 10 to 30% (22)(23)(24)(25)(26) of PLWH in the United States (US). Observational evidence supports an association between HCV and clinically evident CVD, in both the general population (27,28) and in PLWH (29). Yet studies in the general population focusing on the role of HCV in coronary artery disease risk are inconclusive (27) and, when restricting to MI only, have generally not supported an association (30)(31)(32)(33).…”
Section: Word Count: 2736 Wordsmentioning
confidence: 99%
“…(39,40) Both infections are associated with elevated cardiovascular risks, with coinfected patients presenting an even higher risk than their HIV-monoinfected counterparts, possibly mediated through synergetic persistent inflammation, microbial translocation, or elevated "traditional" risk factors such as blood pressure. (41) It has been suggested that NAFLD partially mediates CVD risk in HIV patients (2) and that the relationship between HCV and atherosclerosis is mediated by steatosis. (5) In the general population, an FLI ≥ 60 has been associated with the risk of stroke in men.…”
Section: Discussionmentioning
confidence: 99%
“…A backward procedure based on the Wald test was used to select the adjustment variables kept in the final multivariable model (threshold of significance set at P ≤ 0.05). The final multivariable model was adjusted for gender and three age categories (40)(41)(42)(43)(44)(45)(46)(47)(48)(49), and ≥50 years), irrespective of their P values. We tested for the presence of confounding factors: each nonsignificant variable was tested for its potential confounding effect in the multivariable model, i.e., whether the inclusion of that variable changed at least one of the coefficients of the other variables by >25%.…”
Section: Statistical Analysesmentioning
confidence: 99%